Aktivitas Hubungan Masyarakat Universitas Negeri Berdasarkan Teori - Rachmat Kriyantono (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
This study aims to describe how the public relations activities of state universities in carrying out their functions. The standard of activity is based on the Theory of Excellence. The quality of public relations activities is very important related to the era of public information openness which requires universities to conduct public services well as part of good governance. Theory of Excellence is the most dominating theory of public relations studies in the world as a normative standard for good public relations practice. This study uses a survey method by distributing questionnaires to 59 public relations practitioners of state universities. The research also interviews three practitioners to detail data from questionnaires. This research results in finding that the principles of Excellence Theory have begun to be adopted by public relations practitioners. Symmetrical two-way communication strategies have also been found although there is still more focus on the external public. Other findings, PR activities have been included as part of management activities and dominant coalition in state universities. This research is expected to contribute to the development of public relations studies in the Indonesian context.